A multisystem syndrome compatible with systemic lupus erythematosus: Case report and review of literature - Samira Alesaeidi; Morteza Daraei; Amir Salami khanshan; Hamed Zainaldain (Babol University of Medical Sciences, 2021)
Background: Abdominal pain is a routine symptom. Mesenteric arteritis, intestinal vasculitis, enteric vasculitis, mesenteric vasculitis, lupus peritonitis, and abdominal serositis are the possible differential diagnoses. Therefore, lupus enteritis has an uncertain outbreak. Case Presentation: A 27-year-old woman presented with clinical presentation of peritonitis suggestive of acute abdominal crisis with three days history of fever, bloody diarrhea, nausea, vomiting and seizure. Further work up revealed microangiopathic hemolytic anemia, thrombocytopenia, proteinuria, polyserositis and her initial autoimmune panel all were negative. Since SLE was at the top of our diagnosis, we considered glucocorticoid and cyclophosphamide pulse therapy. After approximately two months of her initial presentation, when all of her symptoms subsided by initial therapy, her antinuclear antibody became positive at 1:320 titers and renal biopsy was compatible with lupus nephritis (stage III). Conclusion: It is crucial to take the diagnosis of lupus into consideration, in case of any young female with multiorgan involvement even without positive antibody tests. As in this case, it took more than two months after initial presentation to confirm the diagnosis via renal biopsy and only after then, serum autoantibodies became seropositive